Protective Effect of Celastrus paniculatus Seed Extract against Lead Acetate Induced Nephrotoxicity in Wistar Rats - Balaji, Karunakaran; Vijayakumar, J; Senthilkumar, Sivanesan; Vijayaraghavan, Rajagopalan; Naveenkumar, Viswanathan (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The plant Celastrus paniculatus is used in the traditional medical practices of India to treat a plethora of diseases. Earlier research on the plant revealed several biological properties and interesting bioactive compounds with significant medicinal uses. Materials and Methods: In this study, the ethanolic extract of the seeds of the plant (EECP) has been investigated against lead acetate (LA) induced nephrotoxicity in Wistar rats. Thirty rats were divided into five groups (n=6) wherein group 1 that contained normal animals served as control while group 2 received LA (30mg/kgb.w/day, p.o.). Animals in groups 3 – 5 received respectively the standard drug N-acetylcysteine (NAC, 200mg/kg b.w/day, p.o.) and EECP in two doses (400and 800mg/kgb.w/day, p.o.) together with LA (30mg/kg b.w/day, p.o.) for 28 consecutive days.On day 29, all the animals were sacrificed and the blood and kidney were collected for analysis. Results and Conclusion: LA significantly decreased the level of catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), reduced glutathione (GR), glutathione S-transferase (GST) and glutathione (GSH) and increased the level of hydrogen peroxide (H2O2), hydroxyl radicals (OH-) and lipid peroxidation (LPO) as compared to those in control rats. Administration of EECP especially 800mg/kg b.w. significantly downregulated the serum urea, creatinine and KIM 1 levels and also the level of oxidative stress markers when compared to the LA group. Histological and immunohistochemistry (KIM 1) study showed a significant change in the cytoarchitecture of the renal tissue thereby revealing the pro-active role of C. paniculatus seeds in nephrotoxicity.
Keywords: Celastrus paniculatus seeds; Free radical scavenging activity; KIM 1; Lead Acetate; Nephro-toxicity; Wistar rats